Interlanguage Paragmatics of Disagreement by Indonesian EFL Learners - Aisyah, Annis Syafa'atun, Agus Wijayanto, P.hD, Dr. Dwi Haryanti, M.Hum (2015)
The research paper studies about disagreement strategies, gender difference, and politeness strategies by Indonesian EFL Learners. The study aims at describing disagreement strategies used by Indonesian EFL Learners and describing the gender difference influence on disagreement strategies and determining the politeness strategy used in disagreement by Indonesian EFL Learners. The research paper is a descriptive qualitative research. The data are sentences containing disagreement strategies in the data source which is disagreement. The data sources are from Discourse Completion Task (DCT) and its responds. The data are collected from 20 male 20 female students of Department of English Education. The researcher applies comparison in analyzing the data of the study then review the raters. The results of the research show that: out of 360 data using disagreement strategies, the use combination of Contradictions and Counterclaims 304 data or 84,45%, Counterclaims 46 data or 12,78%, Contradictions 3 data or 0,83%, Challenges 1 data or 0,27%, the combination of Counterclaims and Contradictions 3 data or 0,83%, the combination of Challenges and Counterclaims 3 data or 0,83%, the combination of Challenges, Contradictions and Counterclaims 1 data or 0,27%. The gender difference use in combination of Contradictions and Counterclaims female 142 data or 39,3%, male 162 data or 44,95%, contradictions, male 3 data or 0,83%, Counterclaims female 33 data or 9,1%, male 12 data or 3,27%, Challenges male 1 data or 0,27%, combination of Challenges, Contradictions and Counterclaims female 1 data 0,27%, combination of Counterclaims and Contradictions female 2 data or 0,56%, male 1 data or 0,27%, combination of Challenges and Counterclaims female 2 data or 0,56%, male 1 data or 0,27%. The use of politeness strategies Bald on record 238 data or 66,11%, Negative Politeness 94 data or 26,11%, Positive Politeness 9 data or 2,5%, Off record 19 data or 5,27%. From these precentage, it can be concluded that the participants used the combination of Contradictions and Counterclaims more oftenly. The gender difference influence that Male more often used the combination of Contradictions and Counterclaims that did female. The participants more often used Bald on record that did Positive Politeness.